2012
DOI: 10.2169/internalmedicine.51.7236
|View full text |Cite
|
Sign up to set email alerts
|

Glycated Albumin to Glycated Hemoglobin Ratio is a Sensitive Indicator of Blood Glucose Variability in Patients with Fulminant Type 1 Diabetes

Abstract: Background Since serum albumin is glycosylated more rapidly than hemoglobin, it is possible that the glycated albumin (GA) to HbA1c ratio (GA: HbA1c ratio) is potentially a more sensitive indicator of blood glucose excursion than HbA1c. The aim of the present study was to assess the clinical usefulness of GA: HbA1c ratio as a marker of daily glucose excursions in patients with type 1 diabetes according to the subtypes; acute onset type 1A, fulminant and slowly progressive type 1 diabetes. Methods Fifty-six out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…A recent study reported that GA may reflect not only the average glucose level, but also glucose fluctuations and postprandial glucose excursions. 32 Our findings are consistent with these results. Because GA levels increase as blood glucose levels rise 33 and the rate of GA level increase is 10 times faster than that of hemoglobin, 34 serum GA levels may also be affected by temporary blood glucose spikes.…”
supporting
confidence: 93%
“…A recent study reported that GA may reflect not only the average glucose level, but also glucose fluctuations and postprandial glucose excursions. 32 Our findings are consistent with these results. Because GA levels increase as blood glucose levels rise 33 and the rate of GA level increase is 10 times faster than that of hemoglobin, 34 serum GA levels may also be affected by temporary blood glucose spikes.…”
supporting
confidence: 93%
“…Accordingly, GA is used as an index of short-term glycemic control [2]. For example, the GA : HbA1c ratio has been suggested to be a better marker of glycemic variability than HbA1c in type 1 diabetes, especially in fulminant type 1 diabetes [3]. Importantly, a few past studies have suggested that HbA1c is closely associated with the fasting plasma glucose level, while GA is more closely associated with the postprandial plasma glucose level, compared with the HbA1c level [4][5].…”
mentioning
confidence: 99%
“…15,16 Recent research suggested that GA:HbA 1c ratio rather than GA itself has been reported to be a useful index of glucose excursion and is related to beta cell function. 22,24 These findings suggest that GA:HbA 1c ratio measurements may be helpful in indicating DN in patients with diabetes. However, until now, there was little research on GA:HbA 1c ratio function for DN presence.…”
Section: Discussionmentioning
confidence: 85%
“…It has been reported that the GA:HbA 1c ratio is more closely associated with postprandial plasma glucose levels and insulin secretory function than HbA 1c . Recent research suggested that GA:HbA 1c ratio rather than GA itself has been reported to be a useful index of glucose excursion and is related to beta cell function . These findings suggest that GA:HbA 1c ratio measurements may be helpful in indicating DN in patients with diabetes.…”
Section: Discussionmentioning
confidence: 92%